2015
DOI: 10.1159/000369698
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Interferes with the Proliferation and Differentiation of Neural Stem Cells in the Subventricular Zone of Neonatal Rats

Abstract: This is an Open Access article licensed under the terms of the Creative Commons AttributionNonCommercial 3.0 Unported license (CC BY-NC) (www.karger.com/OA-license), applicable to the online version of the article only. Distribution permitted for non-commercial purposes only. Previous studies have shown ketamine can alter the proliferation and differentiation of neural stem cells (NSCs) in vitro. However, these effects have not been entirely clarified in vivo in the subventricular zone (SVZ) of neonatal rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…Therefore, we investigated the effects of ketamine on NSCs obtained from embryonic day 18 rat anterior cortices. Recent studies have shown that ketamine alters the proliferation and differentiation of NSCs [29]. However, the effects of ketamine on NSCs were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated the effects of ketamine on NSCs obtained from embryonic day 18 rat anterior cortices. Recent studies have shown that ketamine alters the proliferation and differentiation of NSCs [29]. However, the effects of ketamine on NSCs were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…injection of ketamine or multiple (six times) consecutive i.p. injections of ketamine at 1-h intervals, based on the methods described in previous studies (Huang et al, 2015, 2016), with modifications. For both single and multiple administrations, mice were randomly assigned to five groups, with 12 mice per group: saline-treated group, 10 mg/kg ketamine group, 20 mg/kg ketamine group, 40 mg/kg ketamine group, and 80 mg/kg ketamine group.…”
Section: Methodsmentioning
confidence: 99%
“…In each section, measurements were performed in 5 regions, and planar area enclosed by each region was 50 μm×50 μm. The edges of the regions were defined based on structural details within the tissue section to ensure that fields did not overlap [30]. The density of positive cells was presented as the total number of positive cells within the SVZ and SGZ.…”
Section: Immnofluorescence Stainingmentioning
confidence: 99%